THE INFLUENCE OF PARTICIPATORY LEADERSHIP STYLE MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE PT. TRANS PIRAMIYD BALIKPAPAN - Sudarmo, Sudarmo; Hasan, Syahril; Sutrisno, Hadi (Visioner : Jurnal Manajemen dan Bisnis, 2022)
This study aims to understand whether Participatory leadership style, motivation and Work Discipline on Employee Performance at PT. Trans Piramyd Balikpapan on purpose and situation, sponsored by software that uses the SPSS version 18 windows, has a significant importance on the performance of the employees of PT. Trans Piramyd Balikpapan is dominant on employee performance partially. Leadership is the ability of a person for the purpose of a group or organization that has been determined. The purpose of this study was to study the presence or absence of the influence of Participatory Leadership style, Motivation and Work Discipline of PT. Trans Piramyd Balikpapan, is maximize by measuring the magnitude of this influence. The method used in this research is to use quantitative data obtained through 86 respondents are samples then processed using statistics then presented in the form of scientific analysis. After collecting data through both questionnaires, field observations using multiple linear regression analysis, where the regression analysis is: Y = 0.316 X1 + 0.343 X2 + 0.222 X3 Participative leadership style variables, motivation and work discipline have no significant effect on employee performance. F-count obtained is = 1.544> F table 0.209. The partially dominant support for the performance of employees of PT. Trans Piramyd Balikpapan is the highest-value work discipline, amounting to 0.042 with a t value of 2.062> 0.178 table values.